Language Style in Forming Family Identity on Klem Family YouTube - Rahmi Wulansari; Ice Sariyati; Fourus Huznatul Abqoriyyah (Journal of English Language and Education, 2026)
Language style plays an important role in shaping and expressing family identity, especially in digital media such as YouTube, where private interactions become public representations. However, previous studies have not sufficiently explored how figurative language contributes to constructing family identity in online family vlogs. Drawing on semantic and figurative language theory, this study aims to identify the types and functions of language style used by the Klem Family in their YouTube content. A qualitative descriptive method with a case study approach was employed, analyzing utterances through transcription and classification based on semantic theory. The findings reveal 42 instances of figurative language, consisting of 9 similes, 29 hyperboles, and 4 personifications, with hyperbole as the dominant feature. These language styles function to clarify meaning, express emotions, and create imaginative effects that strengthen family identity. In conclusion, language style not only facilitates communication but also plays a significant role in constructing closeness and identity in digital family interactions.